OP0170 USE OF THE PROVISIONAL EULAR/ACR IGG4-RD CLASSIFICATION CRITERIA IN A COHORT OF SPANISH PATIENTS. (June 2019) - Fernandez-Codina, Andreu; Pinilla, Blanca; Pinal-Fernandez, Iago; Feijoo-Masso, Carlos; Lopez-Dupla, Miguel; Fonseca, Eva; Orozco-Galvez, Olimpia; Martínez-Valle, Fernando; ,
Abstract : Background: The ACR/EULAR IgG4-related disease (IgG4-RD) provisional classification criteria were presented at the ACR conference in 2018. The performance of these criteria in a fully non-Asian cohort is unknown. Objectives: To explore the performance of these provisional criteria in a cohort of Spanish patients with IgG4-RD. Methods: Data were obtained from the Spanish IgG4-RD registry (REERIgG4) from October 2013 to December 2018, including 9 centers. Patients needed to fulfill almost 1 of the available diagnostic criteria sets (pathology consensus and/or comprehensive). N provisional ACR/EULAR classification criteria (PAECC) were applied based on the public information disclosed at the abovementioned meeting. Results: One-hundred patients were included. Thirty-four (34%) were females, median age at diagnosis was 54.8 years (IQR 20.7). The ethnicity of the participants was: Caucasian 83%, Hispanic 12% and North-African/Middle-East 5%. Ninety-two percent were diagnosed with a biopsy. Regarding the diagnostic criteria, 85% met consensus pathology criteria and 94% comprehensive criteria. Fifty-one patients (51%) had systemic IgG4-RD involving >1 tissue. The most commonly involved tissues were: retroperitoneum (35%), lymph nodes (19%), orbit pseudotumor (18%), salivary glands (16%) and pancreas (14%). Forty-two patients (42%) had elevated serum IgG4. Seventy-one individuals (71%) met the PAECC including entry criteria, exclusion criteria with an inclusion criteria score equal or >19 points. From the 29 cases that did not meet the PAECC, 9 (31%) did not fulfill the first step (entry). Those patients had rarer organs involved as hypophysis, mesenterium or jaw. Eight patients (28%) met one of the exclusion items. Two had positive antineutrophil cytoplasmic antibodies, 2 steroid resistance, 2 double-stranded anti-deoxyribonucleic acid antibodies, 1 other specific autoantibodies, 1 eosinophilia and fever. None of them had evidence of active connective tissue disease, vasculitis, malignancy or infection. Finally, 16 of the patients who did not meet the PAECC (55%) had an inclusion criteria score under 19 points (median 12): 3 (19%) did not have a biopsy, 8 (50%) biopsies had partial reports, and 10 subjects (62.5%) had normal serum IgG4 levels. Six (38%) of them had involvement limited to the head and neck and 3 (19%) had retroperitoneal or aortic involvement. Conclusion: Seventy-one percent of the Spanish patients participating in the REERIgG4 met the 2018 PAECC, while all of them met almost one of the previous diagnostic criteria. Populations with non-Asian ancestry might get lower scores, as they would make less points in significant domains (serum IgG4, pancreatic-biliary) or have presentations that may grant lower scores or exclusion. Enforcing complete pathology reports might increase the scores. Nevertheless, the new classification criteria are provisional and primarily intended for clinical trial recruitment, focusing in the most common manifestations. Therefore, the preexisting diagnostic criteria should be used for standard clinical purposes. Reference: [1] Wallace Zs, Naden RP, Choi H. The 2018 ACR/EULAR Classification Criteria for igG4- Related Disease. Submitted 2018. Disclosure of Interests: None declared